STRATEGI KEPALA MAN GUNUNG PADANG PANJANG DALAM MENINGKATKAN NILAI AKREDITASI LEMBAGA - Syaiful Arifin (IAIN Batusangkar, 2018)
This reaserch was done to know about the Strategy headmaster MAN Gunung Padang Panjang increasing value of accreditation.This study uses a qualitative method using a case study perspective deskriptif.Teknik data collection in the form of observation, interviews and documentation study.The results of this study, 1). Strategy headmaster in improving the value of accreditation: a) Establish a madrasah accreditation team. b) Uniting the whole perception of madrasah stakeholder to increase the value of accreditation. c) develop a vision and mission and strategic plan of the madrasah. d) Inviting community leaders actively promote madrasah.e). Every effort to improve education standard eight 2). Barriers faced by the headmaster is: a) The attitude of teachers varies proactive in achieving the implementation of the vision and mission of the madrasas., B). Professionalism of teachers who have not honed well. c). There are still teachers who like comfortable or just come madrasah when teaching hours. d). There is still a teacher less concerned about the activities of the madrasas, facilities and infrastructure is not yet complete. 3). Implementation of the strategy undertaken headmaster: a) Make a commitment with educators and stakeholders to advance the institution, b) Develop EDS, c) vision and mission madrasah, d) .make strategic plan, e) Establish Accreditation Team , f) empower school committee,and g) to collaborate with relevant agencies.